2001
DOI: 10.1097/00005537-200106000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Regional Metastases, Distant Metastases, and Second Primary Malignancies in Squamous Cell Carcinomas of the Larynx and Hypopharynx

Abstract: Conclusions are as follows: 1) The incidence of second primary tumors is independent from the primary tumor staging and distant and delayed regional metastases. The highest incidence occurred in patient groups with the highest disease-free survival rates (P =.0378). 2) Highest incidence of delayed and distant metastases occurred in hypopharyngeal tumors and was three times greater than in laryngeal cancers (P =.028). 3) Salvage therapeutic rates were poor for delayed metastases to the ipsilateral treated nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
198
6
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(229 citation statements)
references
References 29 publications
16
198
6
9
Order By: Relevance
“…Loco-regional relapse was the predominant pattern of failure in accordance with previously published series on HNSCC [13,15] and the authors' own experiences [2]. The crude incidence of distant metastases and metachronous second primaries in this single institution study was abnormally low at 4% and 2% respectively in contrast to 20 Á 26% reported from earlier large cohorts [5,17]. Potential biases and limitations of a retrospective study with a short median follow-up may be a possible explanation for this Both these events occur late in the natural history of hypopharyngeal cancers, hence careful and long follow-up is necessary for their detection.…”
Section: Discussionsupporting
confidence: 90%
“…Loco-regional relapse was the predominant pattern of failure in accordance with previously published series on HNSCC [13,15] and the authors' own experiences [2]. The crude incidence of distant metastases and metachronous second primaries in this single institution study was abnormally low at 4% and 2% respectively in contrast to 20 Á 26% reported from earlier large cohorts [5,17]. Potential biases and limitations of a retrospective study with a short median follow-up may be a possible explanation for this Both these events occur late in the natural history of hypopharyngeal cancers, hence careful and long follow-up is necessary for their detection.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, the crude overall survival probability of HNSCC patients, as tracked with OCS, never achieves equivalence with the noncancer population, as some risk of dying from the index cancer, or associated sequelae, is 'overlaid' in addition to other possible causes of death. [21][22][23][24] The observation that mortality probability (as expressed by OCS) plateaus at 3 years may afford the use of 3-year clinical trial survival data as a valid endpoint, as the patients' probability of 5-year survival is thereafter somewhat static. However, this observation should be validated with established clinical datasets 25,26 in order to verify that trends observed in historic epidemiological datasets, such as SEER, are verified in more recent prospective series.…”
Section: Discussionmentioning
confidence: 99%
“…However, the survival of patients with advanced disease stage has not improved. The main causes of death are represented by the recurrence of loco-regional disease and the appearance of distant metastases not responding to conventional treatments [1]. At present, diagnostic and clinical studies fail to differentiate patients without metastasis or with regional occult metastasis and patients more likely to undergo metastasis from patients with longer overall survival time (OS).…”
Section: Introductionmentioning
confidence: 99%